Efficacy of Mentha aquatica L. Essential Oil (Linalool/Linalool Acetate Chemotype) against Insect Vectors and Agricultural Pests - Marta Ferrati; Eleonora Spinozzi; Cecilia Baldassarri; Filippo Maggi; Roman Pavela; Angelo Canale; Riccardo Petrelli; Loredana Cappellacci (MDPI AG, 2023)
In recent years, agrochemical industries have been focused on the development of essential oil (EO)-based biopesticides, which can be considered valuable alternatives to traditional chemical products. The genus Mentha (Lamiaceae) comprises 30 species characterized by a wide range of biological activities, and some of their EOs showed good potential as pesticidal agents. In this regard, the aim of this study was to evaluate the insecticidal activity of the EO obtained from a rare linalool/linalool acetate chemotype of Mentha aquatica L. The EO was found to be highly effective against Culex quinquefasciatus (Say) 2nd instar larvae, Metopolophium dirhodum (Walker) adults, Spodoptera littoralis (Boisduval) 2nd instar larvae, and Tetranychus urticae (Koch) adults, showing lethal concentrations (LC50) or doses (LD50) of 31.5 ± 2.2 µL L−1, 4.9 ± 0.8 mL L−1, 18.5 ± 2.1 µg larvae−1, and 3.3 ± 0.5 mL L−1, respectively. On the contrary, Musca domestica L. adults and 3rd instar larvae of C. quinquefasciatus and S. littoralis were moderately affected by the treatment (LC50 or LD50: 71.4 ± 7.2 µg adult−1, 79.4 ± 5.2 µL L−1, 44.2 ± 5.8 µg larvae−1, respectively). The results obtained in this work demonstrated that various insects and pests could be differently sensible to the same EO and may lead to the exploitation of this plant or its major volatile compounds as novel ingredients of botanical insecticides and pesticides.